2022
DOI: 10.1111/ases.13045
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term outcomes of single‐incision laparoscopic surgery for right colon cancer: A multicenter propensity score‐matched analysis

Abstract: Introduction Single‐incision laparoscopic surgery (SILS) for colon cancer is a recent innovation in minimally invasive surgery that can improve short‐term outcome. However, several biases exist in current favorable comparisons of SILS with conventional laparoscopic (CL) surgery. Moreover, the oncological outcomes in SILS remain unclear. The aim of this study was to identify outcomes following SILS and CL for right colectomy using a propensity score‐matched analysis. Methods A total of 553 patients underwent cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Furthermore, SILS reportedly achieves a better cosmetic effect and less postoperative pain than conventional multiport laparoscopic surgery for ascending colon cancer, sigmoid colon cancer, and rectosigmoid cancer 17 . Although right hemicolectomy requires a lot of vascular treatment, SILS reportedly has a shorter operative time than conventional laparoscopic surgery 18,19 . Therefore, it seems that even complicated procedures such as LCA preservation can be performed via SILS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, SILS reportedly achieves a better cosmetic effect and less postoperative pain than conventional multiport laparoscopic surgery for ascending colon cancer, sigmoid colon cancer, and rectosigmoid cancer 17 . Although right hemicolectomy requires a lot of vascular treatment, SILS reportedly has a shorter operative time than conventional laparoscopic surgery 18,19 . Therefore, it seems that even complicated procedures such as LCA preservation can be performed via SILS.…”
Section: Discussionmentioning
confidence: 99%
“…17 Although right hemicolectomy requires a lot of vascular treatment, SILS reportedly has a shorter operative time than conventional laparoscopic surgery. 18,19 Therefore, it seems that even complicated procedures such as LCA preservation can be performed via SILS.…”
Section: Discussionmentioning
confidence: 99%
“…In Japan, a prospective cohort study on robotic surgery for colon cancer demonstrated the safety and curative potential of the surgical system [ 3 ]. The world's first minimally invasive single-incision laparoscopic surgery (SLS) was reported in 2008 [ 4 ], and many studies have shown its safety and favorable oncologic outcomes compared with those of multiport laparoscopic surgery [ 5 8 ]. The da Vinci SP system (Intuitive Surgical Inc., Sunnyvale, CA, USA) is a specialized surgical platform that enables single-port robot-assisted surgery.…”
Section: Introductionmentioning
confidence: 99%